Comparative study of Pap smear abnormalities in HIV infected and HIV non-infected women - V. N., Kusumam; A., Naseema Beevi; Sreenivas, Smitha; A. M., Nurul Ameen; Menon, Vidya R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: HIV positive women are more likely than HIV negative women to have cervical dysplasia. Incidence of HPV-related dysplasia increases as immune function declines. To analyse the prevalence of cervical dysplasia on papsmear among women affected with HIV and to compare with that of HIV negative women. Methods: The study period was of 6 months duration from December 2010 to May 2011. Cervical cytology specimen from HIV positive and HIV negative women who attended the OPD of Institute of Maternal and Child Health, Government Medical College, Kozhikode. Were collected after excluding known case of carcinoma cervix, post hysterectomy patients, patients with bleeding per vagina and also those with active genital tract infections. Results: A prospective study of 200 females (100 HIV positive and 100 HIV negative) was done in our hospital. Age range was between 36 and 50 years. PAP smear abnormality was obtained in 35% of the study group. Out of which 21% was seen in HIV positive patients and 14% in HIV negative patients. Prevalence of LSIL (low grade squamous intraepithelial lesion) was significantly higher among HIV positive patients. Abnormality was not associated with CD4 count, HIV status of husband or addictions of husband, not associated with number of partners of husband both in HIV positive and negative patients. Conclusions: PAP smear abnormality (overall), prevalence of LSIL was significantly higher among HIV positive patients. It was not associated with SES, age of first intercourse, number of partners of wife and other immunosuppressive status.